Evaluation of feasibility accuracy and safety after 79 O-ARM based stereotactic brain biopsies - Inès Bouscatel; Benoit Marlier; Claude-Fabien Litré; Valéry Batchinsky-Parrou; Maxime Rivollier; Stanislas Loniewski; Jean-Charles Kleiber (Scientific Reports)
Abstract Frame-based Stereotactic Brain Biopsy (FSBB) is a minimally invasive procedure with a view to increasing the diagnostic yield. The aim of this study was to investigate the accuracy and safety of FSBB with the help of the intraoperative 3D O-ARM system. A preoperative MRI allowed for targeting the tissue to be sampled. A Leksell stereotactic frame was bolted to patient’s skull in the operating room, and we proceeded to the intraoperative 3D O-ARM acquisition. A software platform was used to calculate stereotactic coordinates through combining both exams. A second 3D O-ARM acquisition was performed to control the final needle target point. A total of 79 patients were included in our study population, 68 biopsies (86.1%) yielded the diagnosis. Biopsy-related complications occurred in 11 patients (13.9%), of whom 8 were successfully diagnosed. Per and post-procedure complications occurred in 3 (3.8%) and 8 cases (10.1%) respectively. Mean operating time was 102 min. FSBB using the intraoperative 3D O-ARM system is a promising alternative. The rate of non-contributory biopsies is moderate given that this new procedure is conducted in the operating room from beginning to end. Complications were not directly linked to the procedure and does not compromise the diagnosis.